Determinants of health related quality of life among type 2 diabetic patients attending National University of Malaysia medical centre / Aqil Mohammad Daher - Mohammad Daher, Aqil (2014)
Diabetes Mellitus is notorious for its metabolic effect, acute and long term complications and impact on Quality of Life (QOL). Plethora of literature has documented the negative impact of DM on QOL. Currently, religion and spirituality constitute a topic of great importance to most of the world’s population where researchers have notably focused attention on the relationship between religion, spirituality and Quality of Life (QOL). However there is little, if none is known about the relationship of spirituality and diabetes-related QOL. The primary aim of this study was to determine factors affecting QOL among sample of patients with type 2 diabetes mellitus attending the medical centre of National University of Malaysia, Kuala Lumpur, Malaysia specifically in relation to spirituality. For this purpose we had to translate the English version of Spiritual Wellbeing Scale (SWBS) into Malay language as well as validate the Malay version of SWBS among Malaysian general population at Klang Valley and thence we proceeded to measure diabetes-related QOL among diabetic patients at the National University of Malaysia Teaching Hospital. Two questionnaires were used in this study; the Malay version of Spiritual Wellbeing Scale and the Audit of Diabetes Dependent Quality of Life (ADDQOL-18). The Malay SWBS is made of 20 items rated on 6 point Likert scale. The ADDQOL-18 is composed of two overview items and 18 life domains which are rated for both impact of diabetes and importance to diabetic patients. Data for the validation phase were collected from 623 Malaysians from three main ethnic groups in Klang valley by trained enumerators. Data for measuring diabetes-related QOL was collected by trained research assistant from 256 patients with type 2 DM who were attending diabetes clinic at the National University of Malaysia Medical Centre. Descriptive statistics were produced for all study variables. Exploratory factor analysis with promax rotation was used to explore the factor structure of the Malay SWBS and determine the reliability coefficient. Stepwise multiple linear regression was used to identify factors associated with diabetes QOL. The results of the study showed an equivalent translated version of the Malay SWBS .The validity of the Malay SWBS was ascertained with the findings of three factors model explaning 59.70% of the total variance, and a reliability coefficient of more than 0.7. Diabetic patients had high proportion of diabetes complications, poor glycemic control, hypertension and obesity. The QOL among diabetic patients in this study was negatively affected. Multiple linear regression showed that glycaemic control (HbA1c), diabetes worry, use of insulin, more than 10 years’ duration of diabetes, neuropathy and retinopathy were associated with poor quality of life, whereas being satisfied with waiting time for consultation and being spiritually affiliated, were associated with better QOL. We concluded that the QOL among the study sample was negatively affected by diabetes. Measures to reduce diabetes complications through better glycemic control and well-tolerated treatment modality, and reducing waiting time would go a long way to improve the quality of life. The positive relation of spirituality to QOL among diabetic patients opens new vista for further research in the field.